Phoenixin Expression Is Regulated by the Fatty Acids Palmitate, Docosahexaenoic Acid and Oleate, and the Endocrine Disrupting Chemical Bisphenol A in Immortalized Hypothalamic Neurons - McIlwraith, Emma K.; Loganathan, Neruja; Belsham, Denise D. (Frontiers in Neuroscience, 2018)
Phoenixin (PNX) is a newly identified reproductive peptide required for the estrus cycle. It is most highly expressed in the hypothalamus, where it is a positive regulator of gonadotropin-releasing hormone (GnRH) and kisspeptin. However, it is unknown what signals lie upstream of Pnx to coordinate its effects on GnRH and kisspeptin. We investigated the effects of the hormones, estrogen and leptin; the fatty acids, palmitate, docosahexaenoic acid (DHA), oleate and palmitoleate; and the endocrine disrupting chemical BPA on Pnx mRNA levels. We also examined whether the signaling pathways of nitric oxide, lipopolysaccharide, cAMP and protein kinase C could alter Pnx expression. Immortalized hypothalamic neurons were treated from 2 to 24 hours with these compounds and Pnx mRNA levels were measured with RT-qPCR. Unexpectedly, only BPA as well as the fatty acids, palmitate, DHA and oleate, could alter Pnx expression; therefore suggesting that Pnx may fulfill a nutrient-sensing role in the hypothalamus. Our study is the first to delineate potential regulators of this novel neuropeptide, and our findings provide some insight into the functional role of PNX in the hypothalamus.